Discourse Between the Markan Text and its Implied Interlocutors: Its Impact on Audience Response to the Salvific Gospel and Christian Ethics (Impact: Journal of Transformation, 2018)
This paper seeks to apply the hermeneutical insights on the Markan text to the extant rhetorical situation in the education sector. The theme of the conference that has called for this paper is “Ensuring Quality Education through Ethical and Value Based Principles: A Focus on Sustainable Development Goal: (SDG 4). The underlying supposition is that the Markan text is a rhetorical communication which can be used to encourage stakeholders in the education sector to uphold work ethics. The study probes the discourse between the Markan text and its implied interlocutors and its impact on audience-response to the gospel that is presumed to have within its teachings Christian ethics. This probe is helpful in identifying both the explicit and implicit interlocutor relationships within the matrix of the Markan discourse. In this study, discourse is understood as the communicative transaction between the interlocutors that are both formed and addressed by the entire Markan text. The salvific gospel was and is both a proclamation of the significance of the salvific episode and Christian ethics. The study is premised on the hypothesis that the Markan text was purposely written to eliminate audience obduracy towards the gospel that was being orally proclaimed. This obduracy is portrayed in Jesus’ controversy with the Jewish leaders and in the retold parable of the sower (Mark 4:1-12). This probe sheds light on how the text of Mark can urge people to uphold ethical standards in different spheres of human endeavour.